Застосування медіації в адміністративному судочинстві: вітчизняний та зарубіжний досвід - Шинкар, Тетяна Ігорівна (Інститут права імені Володимира Великого Міжрегіональної Академії управління персоналом, 2018)
У дисертації проведено комплексне дослідження вітчизняного та зарубіжного досвіду застосування медіації в адміністративному судочинстві. Розглянуто теоретико-правові основи, сутність, підходи та особливості врегулювання юридичних спорів з використанням медіації в адміністративному судочинстві через призму зарубіжного досвіду. Сформульовано пропозиції та рекомендації пов’язані з формуванням законодавчих основ запровадження медіації для вирішення юридичних спорів в адміністративному судочинстві України. В диссертации проведено комплексное исследование отечественного и зарубежного опыта применения медиации в административном судопроизводстве. Рассмотрены теоретико-правовые основы, сущность, подходы и особенности урегулирования юридических споров с использованием медиации в административном судопроизводстве через призму зарубежного опыта. Сформулированы предложения и рекомендации связанные с формированием законодательных основ введения медиации для решения юридических споров в административном судопроизводстве Украины. The thesis conducts a complex study of the national and foreign experience in the application of mediation in administrative proceedings. The paper examines theoretical bases, essence, approaches, and peculiarities of legal dispute resolution with the use of mediation in administrative proceedings through the prism of foreign experience. The thesis justifies the necessity of application of mediation in administrative proceedings, as one of the most effective types of alternative dispute resolution attributed to the competence of the administrative court. The concept of alternative dispute resolution in administrative proceedings is highlighted. Alternative methods and their procedures are classified as competitive and conciliatory. Approaches regarding the allocation of the main benefits of mediation and the benefits of other conciliation procedures in administrative justice have been improved. Approaches to the determination of the functional role of the judge as mediator during mediation in administrative proceedings are highlighted and the content related to its prohibitions and restrictions is disclosed. Additional knowledge and professional skills required for the judge as mediator are determined. It is indicated that today in Ukraine there is no special formalized legislation regulating the implementation of mediation. But at the same time, there is no state formal prohibition for the parties to use mediation. According to article 55, paragraph 4 of the Constitution of Ukraine the state guarantees everyone the opportunity to protect their rights by any means not prohibited by law. Therefore it is stated that Ukraine has a constitutional basis for the implementation of mediation. The author of the thesis supports the statement that while there is no particular law in Ukraine, the legal principles of the implementation of mediation should be determined through the regulations of the existing procedural legislation, including administrative one. At the same time, it is emphasized that nowadays in Ukraine there is a lack of qualified mediators. Therefore the only acceptable form of mediation today is mediation at court, which is a mediation procedure conducted within the framework of the judicial proceedings by a judge or a researcher of the same court who have the appropriate training of the mediator. This form will facilitate the adoption of mediation as an alternative way of dispute resolution before judgment is delivered. It is indicated that in administrative proceeding one of the disputing parties is the subject of power. Thus, the peculiarity of alternative dispute resolution in administrative proceedings is the peaceful settlement of relations between a public authority, on the one hand, and a natural or legal person, on the other. Proposals and recommendations concerning creation of the legislative framework for the application of mediation as the alternative dispute resolution in administrative proceedings in Ukraine are formulated.
Применение медиации в административном судопроизводстве: отечественный и зарубежный опыт
Application of mediation in administrative proceedings: national and foreign experience
Keywords: адміністративне судочинство; медіація; конфлікт; публічний спір; альтернативне вирішення спорів; присудова медіація; суддя-медіатор; административное судопроизводство; медиация; конфликт; публичный спор; альтернативное разрешение споров; присудебная медиация; судья-медиатор; administrative proceedings; mediation; conflict; public dispute; alternative dispute resolution; mediation at court; judge as mediator; 342.127.15